MALL - BASED ENGLISH INSTRUCTION - Sutrisna, I Putu Edi; Ratminingsih, Ni Made; Artini, Luh Putu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Technology integration in English language learning has become a necessity in any educational development. This study aimed at developing Mobile Assisted Language Learning (MALL) based instructional English Sociology course book and measuring the quality of the developed product. The study employed a research and development design as proposed by Sugiyono (2010) and was conducted in Sociology Education Department of Undiksha Singaraja. It involved 2 lecturers and 73 students. The data were collected by means of observation, interview, questionnaire, and document study, which were analysed descriptively. As the results, there were eight units developed in this course book which covered the topics of: introduction, greeting, asking/giving information, family tree, telling time, invitation, preposition of time, giving direction, preposition of place, descriptive text, report text, procedure text, recount text, and exposition text. Three stages of inquiry proposed by Gilbert and Hoepper (2014) were used in developing the course book. Regarding the validity and quality of the product, the results of measurement proved that the content validity of the course book was very high (coefficient validity of 0.98) and the quality of the course book was considered excellent or having a high-quality product where the mean score of the judgment was 4.83 exceeding the criteria of X â¥ 4.18. This indicates that the product of present study is readily used as an instructional material by the students of Sociology Education Department of Undiksha.